Main influencing factors and health-related quality of life issues in patients with oesophago-gastric cancer – as measured by EORTC tools - Tomaszewski, Krzysztof A.; Püsküllüoğlu, Mirosława; Biesiada, Katarzyna; Bochenek, Justyna; Ochenduszko, Sebastian; Tomaszewska, Iwona M.; Krzemieniecki, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: To assess influencing factors and main health-related quality of life (HRQoL) issues in patients with cancers of the oesophago-gastric region using the European Organization for Research and Treatment of Cancer (EORTC) quality of life questionnaire Core 30 (QLQ-C30) and its oesophago-gastric module (QLQ-OG25). Material and methods : Patients were qualified for this study based on the histological confirmation of oesophageal, oesophago-gastric or gastric cancers. Each patient filled out the Polish version of the EORTC QLQ-C30, the QLQ-OG25 module and a personal questionnaire. Patients were divided into groups based on gender, age, treatment intention, tumour localization, working status and level of education. Results: Our study included 112 patients – 39 women (35%) and 73 men (mean age ± SD; 60.2 ±10.9). Thirty-five patients (31.3%) completed the questionnaires twice. Eighty-four (75%) patients had gastric cancer (GC), twenty-six (23.2%) oesophageal cancer (OC) and two (1.8%) cancer of the oesophago-gastric junction (OGJC). Eighty (71.4%) patients underwent surgical treatment prior to either chemo-, radio- or chemoradiotherapy. The Global Health Status scale of the QLQ-C30 inversely correlated with all the other QLQ-C30 and QLQ-OG25 symptom scales (r = –0.26 to –0.61; p < 0.05). Conclusions : The main HRQoL problems of Polish OC, OGJC and GC patients are fatigue, insomnia, anxiety, and appetite and weight loss. Older age, receiving palliative treatment, having gastric cancer, being on retirement and having lower education are factors associated with higher symptom scores (worse symptoms) and thus poorer HRQoL.